Käärmeiden sienitauti – uusi uhka? - Salo Pälvi (Suomen herpetologinen yhdistys ry, 2022)
Snake fungal disease (SFD) is an emerging threat to wild snakes. First identified in 2006, it is caused by the environmental saprobe Ophidiomyces ophiodiicola. The current distribution of SFD is focused on eastern United States, but the fungus has also been diagnosed in wild snakes in Canada and Europe. So far it has been isolated from over 30 different snake species. Several details of the fungus life cycle, environmental and other factors affecting host vulnerability and fungus pathogenicity, and long-term impacts of SFD on snake populations are still unknown. However, SFD poses a serious risk to isolated, small populations of already threatened snake species.